Ecological testing of the winter barley varieties in the conditions of the Republic of Kalmykia - B. A. Goldvarg; M. V. Boktaev; E. G. Filippov; A. A. Dontsova (Зерновое хозяйство России)
Barley productivity varies significantly in various agricultural areas, therefore, there should be conducted an ecological testing to identify varieties’ response to various soil and climatic conditions. That gives an opportunity to identify varieties adapted to specific soil and climatic conditions of a particular area or a region. The purpose of the current study was to conduct an ecological testing of winter barley varieties in the arid central part of theRepublicofKalmykiafor the subsequent identification of the most drought-tolerant, adaptable winter barley varieties, as well as to compare productivity of winter barley with that of spring barley in the arid conditions of the Kalmykia steppes. The study was carried out on the experimental plots of the Kalmyksky RIA named after M. B. Narmaev, a branch of the FSBSI “Pre-Caspian Agricultural Federal Research Center of the Russian Academy of Sciences” (PCAFRC) in 2018–2019. The objects of research were 9 winter barley varieties of various breeding institutions. The variety of winter barley “Erema” was a standard one, the only one from the entire set of studied varieties that has been included into the State List of Breeding Achievements of theRussian Federation, recommended for cultivation in theRepublicofKalmykia. The trials were laid in four sequences with a systematic arrangement of variants. The total area of the plot was60 m2, the registration plot was50 m2. The seeding rate was 350 pcs. Of germinating seeds per1 m2. The forecrop was winter wheat sown in a fallow land. The study has found that the productivity of the varieties “Timofei”, “Romans”, “Sprinter”, and “Molot” were significantly inferior to that of the standard variety. The productivity of the varieties “Espada”, “Kuzen”, “Vivat”, “Samson” were at the same level as of the standard variety. It should be noted that the maximum yield (4.13 t/ha) was produced by the new variety “Vivat” in 2018. The variety has an undoubted prospect to be cultivated in this region, as it is a facultative one according to the biological type of development, unlike the other studied varieties.